Images as qualitative visual references: recommended image boards for product development process activities (Estudos em Design, 2022)
Image Boards (IB) are visual reference tools and their application in the Product Development Process (PDP) is currently concentrated in the early project stages, especially in marketing and industrial design.On the other hand, the current facilities for creating, capturing, selecting, assembling, and sharing images using electronic devices increase the possibility of applying IB in other PDP activities. The aims of this study were to identify the PDP activities in which the IB contributed with information that promote alignment, comparison, or visual inspiration. For this was employed a double quantitative and associative analysis between the PDP activities, images and the IB. The results indicated that the use of images could be beneficial for different PDP activities. Moreover, different PDP activities can be associated with different types of IB. In this sense, the use of IB can offer advantages for multidisciplinary areas of PDP, going beyond design and marketing.
Keywords: Image boards; Qualitative tools; Product development process; Engineering activities